The Determinants of Stunting in Stunting Focus Areas of Sigi Regency: A Study of Risk Factors and Recommendations for Intervention - Nasrul, Nasrul; Hafid, Fahmi; Faisal, T. Iskandar; Taufiqurrahman, Taufiqurrahman; Ramadhan, Kadar (Nutrición Clínica y Dietética Hospitalaria, 2024)
Background: Stunting is a significant health issue in children and Sigi Regency has been recognized as a hotspot for stunting in Central Sulawesi since 2021. The objective of this study is to analyze the determinants of stunting among children aged 0-24 months in Sigi Regency. Methods: Sigi Regency is a district in Central Sulawesi Province, Indonesia. This analytical research utilizes a cross-sectional design. The sample comprises 436 children aged 0-24 months, with their mothers as respondents. The dependent variable is stunting status, while independent variables include mother's age, education level, type of delivery, child's gender and age, source of drinking water, household toilet ownership, early breastfeeding initiation, birth length, birth weight, history of exclusive breastfeeding, current breastfeeding status, food insecurity, number of children, birth spacing, health facility utilization, complementary feeding provision, household smoking, history of illnesses (e.g., acute respiratory infections, diarrhea, pneumonia, tuberculosis, measles), and intestinal parasitic infections. Stunting data is collected by measuring the child's length using Length Board Measuring and age from birth certificates or Child Health Cards. Results: The study found that the significant determinants contributing to stunting in children under two in the stunting area of Sigi District are maternal education <9 years (AOR=2.3, 95% CI: 1.4-3.9), male gender of the child (AOR=1.8, 95% CI: 1.1-2.8), birth length <48 cm (AOR=1.7, 95% CI: 1.0-2.8), low birth weight (AOR=2.2, 95% CI: 1.1-4.5). Conclusion: Implementing educational programs targeting mothers with less than 9 years of education enhances their understanding of nutrition and childcare practices. Emphasize the importance of a balanced diet, with a focus on increasing the intake of animal protein sources